2016
DOI: 10.1172/jci.insight.87535
|View full text |Cite
|
Sign up to set email alerts
|

Repurposing tromethamine as inhaled therapy to treat CF airway disease

Abstract: In cystic fibrosis (CF), loss of CF transmembrane conductance regulator (CFTR) anion channel activity causes airway surface liquid (ASL) pH to become acidic, which impairs airway host defenses. One potential therapeutic approach is to correct the acidic pH in CF airways by aerosolizing HCO3− and/or nonbicarbonate pH buffers. Here, we show that raising ASL pH with inhaled HCO3− increased pH. However, the effect was transient, and pH returned to baseline values within 30 minutes. Tromethamine (Tham) is a buffer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 61 publications
0
29
0
1
Order By: Relevance
“…Inflammation is critical for host defense. Previous studies indicate that in the respiratory system, an acidic pH impairs, and an alkaline pH enhances two host defenses against bacteria, mucociliary transport and antimicrobial activity ( 1 , 2 , 9 , 19 , 66 , 77 , 80 , 88 ). Finding that TNFα and IL-17, important cytokine regulators of neutrophilic inflammation, increase pH ASL emphasizes the importance of an increased pH ASL in defending the respiratory tract.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation is critical for host defense. Previous studies indicate that in the respiratory system, an acidic pH impairs, and an alkaline pH enhances two host defenses against bacteria, mucociliary transport and antimicrobial activity ( 1 , 2 , 9 , 19 , 66 , 77 , 80 , 88 ). Finding that TNFα and IL-17, important cytokine regulators of neutrophilic inflammation, increase pH ASL emphasizes the importance of an increased pH ASL in defending the respiratory tract.…”
Section: Discussionmentioning
confidence: 99%
“…An inhaled β2‐agonist (salbutamol, 200 mg) is then delivered to inhibit any possible bronchoconstriction from the saline inhalation, which is itself a bronchoconstrictive stimulus, and the FEV1 is remeasured. Hypertonic saline aerosol is then inhaled from a Medix ultrasonic nebulizer (previously known as Fisoneb), which has a relatively low output (0.87 mL/min) and a large particle size (5.58 mm aerodynamic mass median diameter) in concentrations of 3% followed by 4% and then 5%, each for an interval of 7 min. At the end of each inhalation, or earlier if symptoms of chest tightness or dyspnea develop, the FEV1 is measured again.…”
Section: Methodsmentioning
confidence: 99%
“…However, more work is required to find out whether the observed viral trapping could indeed be used in antiviral therapy. It had been shown that Tris, called ‘Tromethamine’ in the below citation, administered through nebulization alleviated respiratory problems resulting from cystic fibrosis [ 15 ]; adding the minimally toxic PDS to such solutions might be a way of application.…”
Section: Textmentioning
confidence: 99%